The Legal Politics of Land Ownership and Agrarian Conflict in North Sumatra: Between Legal Certainty and Social Justice - Gerald Elisa Munthe (Rechtsvinding, 2026)
Land conflicts in North Sumatra are structural and ongoing agrarian issues, involving the state, corporations, and indigenous and local communities. These conflicts are triggered by unequal land ownership, overlapping land rights, weak recognition of customary land, and land policies oriented toward investment interests. This article aims to analyze the legal politics of land ownership in North Sumatra and its implications for legal certainty and social justice. The research was conducted using normative legal methods through legislative, conceptual, and case-based approaches. The results of the study indicate that land legal politics do not fully reflect the principles of social justice as mandated by the Basic Agrarian Law (UUPA), thus reinforcing the escalation of agrarian conflicts. A reorientation of land policies is needed that prioritizes the protection of community rights.